1971
DOI: 10.1098/rsta.1971.0040
|View full text |Cite
|
Sign up to set email alerts
|

Wind-induced instability of structures

Abstract: Forms of wind-induced instability of structures are described, and two of these, typical of long bodies with bluff cross-sections, are selected for more detailed consideration. The first is vortex-induced bending oscillation, a type of resonant response to the periodic surface pressure loading caused by the discrete wake vortex street formed from the shear layers separating from the bluff cross-section. Oscillation phenomena are described, including capture of the vortex frequency by the structural response fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 6 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…Following an analysis presented by Parkinson (1971) and others, the displacement of a cylinder under VIV may be expressed by the harmonic response…”
Section: Analytical Modelling and Preliminary Resultsmentioning
confidence: 99%
“…Following an analysis presented by Parkinson (1971) and others, the displacement of a cylinder under VIV may be expressed by the harmonic response…”
Section: Analytical Modelling and Preliminary Resultsmentioning
confidence: 99%
“…Among the various bluff sections, circular, square and rectangular bodies have received more research attention due to their wide application possibilities. Compared to a circular cylinder, prismatic bodies (non-circular) such as square and rectangular sections could pose additional aerodynamic challenges such as the galloping phenomenon [1,2]). Also, these sections (square and rectangular) are successfully employed in a variety of practical situations such as in bridges, buildings and also in marine applications.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly because of this reason, almost all of the studies reported were attempting to disclose various features of these two kinds of oscillation. Parkinson [1] describes different forms of wind-induced instability of structures with bluff sections (including square), including vortex-excitation and galloping. He specifically brought to light the aspect of variation in the configuration of shear layers and the corresponding pressure distribution on the side surfaces.…”
Section: Introductionmentioning
confidence: 99%